Molecular Pathogenesis of BCR-ABL-Negative Atypical Chronic Myeloid Leukemia - Fontana, Diletta; Gambacorti-Passerini, Carlo; Piazza, Rocco (Frontiers in Oncology, 2021)
Atypical chronic myeloid leukemia is a rare disease whose pathogenesis has long been debated. It currently belongs to the group of the myelodysplastic/myeloproliferative disorders. In this review, an overview on the current knowledge about diagnosis, prognosis and genetics is presented, with a major focus on the recent molecular findings. We describe here the molecular pathogenesis of the disease, focusing on the mechanisms of action of the main mutations as well as on gene expression profiling. We present also the treatment options focusing on the emerging targeted therapies.